Da escala médica de saúde à experiência social do saudável :diálogo entre os espaços dos bares e das academias fisiculturistas na cidade do Natal-RN - Pinheiro, Danilo (2005)
Currently, we attend a reverence of concepts ahead as health, life, youth and body. In we widen amount the ideals concerned to the healthful life, to the quality of life, the longevity and joviality and the extremities of the body represented by the illness, for the virus infection, the physical deficiency and the aging. Of the historical shades of the plague, of the hunger and the war that gagged the defenseless individual and its body, in the current days we increase the search for a full and powerful life, independent of a religious imaginary to predict the epidemic curse, the threat represented for the sick people and the incarnate divine anger in the death; or of medical science presented in the spaces of the technology and the physiology, being left fragile the social and psychological dimensions of the human confined to the patient issue and, finally, the commanded urban health politics in quantitative goals of hygienic cleaning, of the medical techniques and the education citizen. For beyond these instances, emerges in our days a plural, close and biographical agreement well of the body and welfare. On the other hand, an understanding of the healthful life and well-being that more certifies the presence of something the one that clear landmarks amongst normality and the irregularity, the esteem and the destructive vice: it has a projection of healthful life measures without conceptual models of body and health under the doctor-scientific standard occidental. This thematic one will confide in way to the enclosure for spaces to the muscles and fitness exercises and the bars from the city of Natal, in the state of Rio Grande do Norte, Brazil, while comprehensive interchange concerning as the individual comes dealing with the notion the body and health and, mainly, if perceiving inside of its body and its health. Amongst these two spaces of typical leisure of the modern urban phenomenon, the hedonism bodily with its muscles and salience and one another form of hedonism in the fruition of allowed drugs will be across itself in a dialogue about which social s relationships are really in game in an imaginary construction amongst an doctor-aesthetic ideal of health and the social and subjective experience in the option for a healthful life